Stories on Adversities of Filipino Teachers as Teachers in the USA: Basis for a Guide on Coping (American Journal of Multidisciplinary Research and Innovation, 2025)
This study explored the adversities of overseas Filipino teachers in public schools at Illinois State. This study utilized a narrative inquiry research design as it aimed to unravel consequential stories of overseas Filipino teachers’ lives as told by them in their own words and worlds. In this qualitative case, the narratives of the overseas Filipino teachers working as teachers in Illinois, the journey of each teacher based on Campbell’s Hero’s Journey framework, and the common adversities across the teachers’ journey were explored through interviews. The study involved six (6) participants, composed of overseas Filipino teachers deployed in different public schools in Illinois State. Prekindergarten through grade 12 students in Illinois attended public schools, which were run by superintendents and school boards who were elected locally. The data analysis tool was thematic, with a specific focus on Campbell’s Hero’s Journey framework. The narratives of overseas Filipino teachers in Illinois reveal their pursuit of better opportunities and professional growth despite financial, cultural, and emotional challenges, with resilience and community support helping them adapt. Their experiences align with Campbell’s Hero’s Journey framework, as they navigate trials, moments of doubt, and ultimate transformation, finding fulfillment in their careers while continuing to evolve and give back. Across the journeys of these six Filipino teachers, common adversities include: Financial Stability and Living Conditions; Personal and Professional Growth; and Emotional and Mental Strain on Teachers.